Tracked Changes. Ships and marine technology. Service personnel for the maintenance, thorough examination, operational testing, overhaul and repair of lifeboats and rescue boats, launching appliances and release gear. General requirements for training providers Part 1, (7th September 2022) - British Standards Institution,
No abstract available